The impact of corporate characteristics on the financial decisions of companies: Evidence on funding decisions by Italian SMEs - Matteo Rossi; Rosa Lombardi; Dario Siggia; Nadia Oliva (Journal of Innovation and Entrepreneurship, 2016)
Small and medium enterprises (SMEs) represent a large percentage of the corporate tissue of developed countries, but they do not have adequate attention. In fact, various researchers have focused their studies on larger and well-known companies. This paper aims to investigate the impact of corporate characteristic on the financial choices of SMEs, with a specific focus on agro-food micro companies. Access to finance is vital in business start-up, development and growth for SMEs, all with very different needs and facing different challenges in terms of finance compared to large companies. The lack of equity invested in small enterprises makes them more dependent on other external sources (e.g. bank loans, overdraft, factoring and leasing). The limitations of the paper are the result of its very nature: it is a largely conceptual paper. Empirical research is therefore needed to test and validate the essentially preliminary framework.
Keywords: 650; Capital structure; Internal source; External source; Bank loans; Agro-food firms; SMEs